Development and validation for multifactor prediction model of sudden sensorineural hearing loss - Zeng, Chaojun; Yang, Yunhua; Huang, Shuna; He, Wenjuan; Cai, Zhang; Huang, Dongdong; Lin, Chang; Chen, Junying (Frontiers in Neurology, 2023)
Background: Sudden sensorineural hearing loss (SSNHL) is a global problem threatening human health. Early and rapid diagnosis contributes to effective treatment. However, there is a lack of effective SSNHL prediction models. Methods: A retrospective study of SSNHL patients from Fujian Geriatric Hospital (the development cohort with 77 participants) was conducted and data from First Hospital of Putian City (the validation cohort with 57 participants) from January 2018 to December 2021 was validated. Basic characteristics, conventional coagulation test (CCT), and blood routine test (BRT) were then collected. Binary logistic regression was used to develop a prediction model to identify variables significantly associated with SSNHL, which were then included in the nomogram. The discrimination and calibration ability of the nomogram was evaluated by receiver operating characteristic (ROC), calibration plot, and decision curve analysis both in the development and validation cohorts. Delong’s test was used for the difference of ROC Curves between the two cohorts. Results: Thrombin Time (TT), Red Blood Cell (RBC), and Granulocyte-Lymphocyte Ratio (GLR) were found to be associated with the diagnosis of SSNHL. A prediction nomogram was constructed using these three predictors. The AUC in the development and validation cohorts was 0.871 (95% CI: 0.789-0.953) and 0.759 (95% CI: 0.635-0.883), respectively. Delong’s test showed no significant difference in ROC Curve between the two groups (D = 1.482, P = 0.141). Conclusion: In this study, a multifactor prediction model for SSNHL was established and validated. The factors included in the model could be easily and quickly accessed, which could help physicians make early diagnosis and clinical treatment decisions.